Gol’dberg Order and Gol’dberg Type of Entire Functions Represented by Multiple Dirichlet Series - Alam, Md Feruj (GANIT: Journal of Bangladesh Mathematical Society, 2011)
We consider the Hadamard product of the class of entire multiple Dirichlet series in several complex variables having the same sequence of exponents. Our object is to study the nature of Gol'dberg order and Gol’dberg type of these functions. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 63-70 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8516